PEMANFAATAN SARANA PENDIDIKAN DALAM PEMBELAJARAN SDN SARIROGO - Taruna Wahyu; Suyadi (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
This research was conducted to determine the use of educational facilities in the process of supporting teaching and learning activities at SDN Sarirogo, Sidoarjo. A qualitative method with a descriptive approach was used in this study and applied data collection methods by observation, interviews and documentation, as well as performing data analysis techniques using triangulation. In the use of educational facilities, we must consider, among other things, the goals to be achieved, the compatibility between the media to be used and the material to be discussed, the availability of supporting facilities and infrastructure, the characteristics of students. With the results of the research that SDN Sarirogo has optimized the use of school facilities in learning, including making the schoolyard a learning medium, and using basketball learning tools in sports lessons. The obstacles to the use of educational facilities include a lack of funding in increasing school assets, a lack of sufficient storage space for school inventories, and a lack of administrative staff to manage educational facilities. Keywords: Pemanfaatan, Sarana Pendidikan, media belajar